2019
DOI: 10.1371/journal.pone.0220702
|View full text |Cite
|
Sign up to set email alerts
|

Human dimensions of wildlife conservation in Iran: Assessment of human-wildlife conflict in restoring a wide-ranging endangered species

Abstract: Human-wildlife conflicts restrict conservation efforts, especially for wide-ranging animals whose home ranges overlap with human activities. We conducted a study to understand conflicts with, and factors influencing the perceived value of an expanding population of onagers ( Equus hemionus onager ) in local communities in southern Iran. We asked about locals’ perceptions of six potential management strategies intended to lessen human-onager conflict. We found that human-onager conflict w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 38 publications
1
16
1
Order By: Relevance
“…In similar systems, crop-raiding conflicts involving the khur subspecies ( E. h. khur ), for example, have recently increased because of natural dispersal of increasing populations into adjacent agricultural landscapes 10 . In contrast to findings from Esmaeili et al (2019) 37 , human-wildlife conflicts in our study area are relatively high (in comparison to past years), especially during dry summers and cold winters when forage is scarce. At such times onagers are forced to leave the protected areas and enter neighboring agricultural lands looking for food.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In similar systems, crop-raiding conflicts involving the khur subspecies ( E. h. khur ), for example, have recently increased because of natural dispersal of increasing populations into adjacent agricultural landscapes 10 . In contrast to findings from Esmaeili et al (2019) 37 , human-wildlife conflicts in our study area are relatively high (in comparison to past years), especially during dry summers and cold winters when forage is scarce. At such times onagers are forced to leave the protected areas and enter neighboring agricultural lands looking for food.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies combining social sciences with habitat connectivity are scant globally 36 . Moreover, there has been little research about human-onager conflict in the study area 37 despite its holding one of the largest remaining populations of Persian onager and also being an area of particularly high human-onager conflict. Hence, our study is one of the first studies that integrated spatial ecology of an endangered species with its human dimensions to facilitate sustainable coexistence.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, now among the most challenging problems is how to restore many critically endangered animal species within the unclear natural limitations of population restoration by captive breeding [ 36 ]. One possible step towards solving this urgent problem could be a bioinformatics model of human diseases on the basis of differentially expressed genes (of domestic versus wild animals) that are orthologs of human genes associated with reproductive potential changes, in order to determine how the anthropogenic environment, compared to natural wildlife, can alter the animal gene expression on the genome-wide scale and thus affect reproductive potential.…”
Section: Introductionmentioning
confidence: 99%
“…Wildlife conflict studies in Iran are rare, and so are the solutions. One domestic survey conducted across three central provinces showed that the human–onager conflict relates to the depredation of crops, such as alfalfa, wheat, and barley [ 75 ]. Another Iranian study used the information from GPS-collared wolves to evaluate the feeding behaviour of wolves and the locality of human settlements in Hamedan province (West) [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…The result of such enhanced conservation activities demonstrated an increase of 17% in the prey population combined with a decrease in poaching violations by 27% in cheetah habitats in 2013–2014 [ 85 ]. In order to discourage the killing of cheetahs, the Department of Environment implemented a monetary compensation scheme of direct payments to herders whose livestock are attacked and killed by wildlife, though compensation is restricted to a few special cases [ 75 ].…”
Section: Discussionmentioning
confidence: 99%